2022
DOI: 10.1080/2162402x.2022.2066609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radio-immunotherapy sequence on immunological responses and clinical outcomes in patients with melanoma brain metastases (ELEKTRA)

Abstract: In patients with melanoma brain metastases (MBM), a combination of radiotherapy (RT) with immune checkpoint inhibitors (ICI) is routinely used. However, the best sequence of radio-immunotherapy (RIT) remains unclear. In an exploratory phase 2 trial, MBM patients received RT (stereotactic or whole-brain radiotherapy depending on the number of MBM) combined with ipilimumab (ipi) ± nivolumab (nivo) in different sequencing (Rad-ICI or ICI-Rad). Comparators arms included patients treated with ipi-free systemic trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The CD45RA is expressed on naive T cells, which respond poorly to recall antigens, and when activated by a foreign or tumor antigen, they lose expression of the CD45RA (25). Increased frequencies of CD45RA-memory T cells were previously shown to be associated with better responses to ICIs in melanoma patients (16). Therefore, the lower frequencies of these T cells in the blood may suggest the absence of tumor-specific T cell memory in younger patients required for a successful ICI treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD45RA is expressed on naive T cells, which respond poorly to recall antigens, and when activated by a foreign or tumor antigen, they lose expression of the CD45RA (25). Increased frequencies of CD45RA-memory T cells were previously shown to be associated with better responses to ICIs in melanoma patients (16). Therefore, the lower frequencies of these T cells in the blood may suggest the absence of tumor-specific T cell memory in younger patients required for a successful ICI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric data of peripheral T-cell frequencies were collected from a previously reported study (ELEKTRA) ( 16 ). The information on frequencies of peripheral T cell subsets in patients with stage IV skin cancer at baseline is available from 71 patients from the ELEKTRA study.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of the optimal sequencing strategy has been performed retrospectively and comprehensive meta-analysis of the accumulated clinical evidence suggested superiority of concurrent over sequential ICI and RT treatment (121). In contrast to the retrospective observations, the prospective single institution ELEKTRA trial demonstrated superiority of RT given prior to ICI treatment, which was reflected by more pronounced increases in circulating CD4 and CD8 cell populations (122). These discrepancies may be related with confounding factors, affecting conclusions of the retrospective trials (122).…”
Section: Clinical Usage Of Radio-and Immunotherapiesmentioning
confidence: 90%
“…In contrast to the retrospective observations, the prospective single institution ELEKTRA trial demonstrated superiority of RT given prior to ICI treatment, which was reflected by more pronounced increases in circulating CD4 and CD8 cell populations (122). These discrepancies may be related with confounding factors, affecting conclusions of the retrospective trials (122).…”
Section: Clinical Usage Of Radio-and Immunotherapiesmentioning
confidence: 90%
“…The authors also noted that anti-PD-1 agents resulted in a greater median volume reduction than their anti-CTLA-4 counterparts. The prospective non-randomized phase 2 study, ELEKTRA, is a considerable investigation into the effects of combination therapies such as pre-ICIs-RT or pre-RT-ICIs on antitumor and peripheral T cell responses in MM patients with brain metastasis(46). Patients with brain metastasis received RT (WBRT or SRS depending on the number of brain metastasis ) in two different sequences in combination with NIVOIPI (RT before or after ICIs).…”
mentioning
confidence: 99%